2011
DOI: 10.1161/circresaha.110.228312
|View full text |Cite
|
Sign up to set email alerts
|

SAP97 and Dystrophin Macromolecular Complexes Determine Two Pools of Cardiac Sodium Channels Na v 1.5 in Cardiomyocytes

Abstract: Rationale:The cardiac sodium channel Na v 1.5 plays a key role in excitability and conduction. The 3 last residues of Na v 1.5 (Ser-Ile-Val) constitute a PDZ-domain binding motif that interacts with the syntrophin-dystrophin complex. As dystrophin is absent at the intercalated discs, Na v 1.5 could potentially interact with other, yet unknown, proteins at this site.Objective: The aim of this study was to determine whether Na v 1.5 is part of distinct regulatory complexes at lateral membranes and intercalated d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
237
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 244 publications
(256 citation statements)
references
References 38 publications
19
237
0
Order By: Relevance
“…This is derived from this work and recent work by Abriel and colleagues (27), who demonstrated that Na V 1.5 associates with syntrophin and SAP97, Makielski and colleagues (5,23), who established that Na V 1.5 coimmunoprecipitates with Cav3 and syntrophin, Vandenberg and colleagues, who showed that Kir2.1 coimmunoprecipitates with syntrophin (11), and Anumonwo and colleagues (28), who assert that Kir2.1 associates with SAP97. This is also in agreement with a recent study by Jalife and colleagues (29), who propose reciprocal modulation of Kir2.1 and Na V 1.5 and suggest that these ion channels are in the same macromolecular complex.…”
Section: Mechanism Of the Effect Of Lqt9 Cav3supporting
confidence: 54%
“…This is derived from this work and recent work by Abriel and colleagues (27), who demonstrated that Na V 1.5 associates with syntrophin and SAP97, Makielski and colleagues (5,23), who established that Na V 1.5 coimmunoprecipitates with Cav3 and syntrophin, Vandenberg and colleagues, who showed that Kir2.1 coimmunoprecipitates with syntrophin (11), and Anumonwo and colleagues (28), who assert that Kir2.1 associates with SAP97. This is also in agreement with a recent study by Jalife and colleagues (29), who propose reciprocal modulation of Kir2.1 and Na V 1.5 and suggest that these ion channels are in the same macromolecular complex.…”
Section: Mechanism Of the Effect Of Lqt9 Cav3supporting
confidence: 54%
“…Among voltage-gated sodium channels, Na v 1.5 has also been reported to interact with SAP97 via its C-terminal PDZ-binding motif, and the amount of Na v 1.5 on the cell surface is decreased in SAP97-silenced myocytes, although the mechanism remains unclear [17].…”
Section: Discussionmentioning
confidence: 99%
“…Originally described in the brain at neuronal synapses (75), there is increasing evidence that these scaffolds play a similar role in the heart (1,7,27,39,45,46,53,61,63,81). It has been shown that interaction of cardiac ion channels with SAP97 occurs with a number of potassium channels including Kv1.5, Kv4, Kir2.2 and 2.3, and the hyperpolarization-activated, cyclic nucleotidegated channels (1,7,27,45,46,61,81).…”
Section: Discussionmentioning
confidence: 99%